Experiments on initial stages of development of dam-break waves - Espartel,Lélis (2021)
ABSTRACT The initial stages of instantaneous dam-break waves are here evaluated spatially and temporally through 36 physical experiments. Different conditions were tested for downstream (J) and upstream (M) water depths and their ratios (r) to approach realistic conditions for prototype dams. Two non-dimensional parameters are proposed – effective height (HEF) and effective velocity (VEF) – to evaluate water depths and velocity peaks along the dam-break wave evolution. The maximum wave height is estimated as a function of r, whereas the HEF is inversely related to r. The maximum VEF peak is registered for r between 0.1 and 0.2, considered a critical description for real dams. The presence of downstream water depth also modifies the dam-break wave frontal shape and types of wave break features. Previously published classifications of the moving wave based on those features are now expanded with a first tested r = 0.8 in which no jet was identified (undulated movement).